A responsabilidade da pessoa jurídica na Lei Anticorrupção - Freitas Junior, Dorival de (2017)
Corruption is a phenomenon present in the many countries reality throughout the world, not being exclusive to Brazil. The consequences of a corrupt act are harmful, especially to society, since the financial resources are diverted or do not enter the public accounts and, as a result, do not return in benefits to the population. Thus, in order to give effect to criminalization laws established in the Conventions signed and ratified by the Brazilian government, and especially after pressure from the popular movements that invaded the streets in 2013, the Act no. 12.846 / 2013 was published, also known as Anti-Corruption Act. Such Act established national or foreign legal entities as active subject of a corrupt act, if they practice acts to the detriment of the Public Administration. The Act also brings as an imputation criterion the objective way to attribute the administrative and civil liability, and shows a new sui generis kind of liability, named judicial liability, leaving out the possibility of criminal liability. However, the Anti-Corruption Act is a clearly criminal law in which practically all the illicit acts in such law and the effects of administrative and judicial conviction have the same effects already prescribed in Brazilian Environmental Crime Act, as well as the illicit acts are described as crimes in the Brazilian Penal Code and apart laws. Since it is not intended to attribute a criminal character to the legal person's liability for corrupt acts, the Act was created contaminated by several unconstitutional issues throughout its text, directly affecting implicit and explicit constitutional principles and guarantees, as well as various specific principles of the criminal law and the procedural criminal law, so that resulting in a totally unconstitutional Act that does not conform to a democratic rule of law